การประกอบธุรกิจข้อมูลเครดิต : รูปแบบกฎหมายที่เหมาะสมสำหรับประเทศไทย - มณีรัตน์ กำจรกิจการ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
Credit Information, itself, plays an important role in the credit system, which is used as an alternative for money in the financial system and the economy. If the credit information does not accurate complete and up to date, it will effect the decision s makers and bring about a massive difficulty. Furthermore, the wrong decisions may cause an economic problem and bring about a financial crisis. Therefore, the need for the right credit information (accurate, complete, and up to date) and the right to privacy of personal data have been raised in order to prevent the rising of non-performing loans (NPLs). As a result, the Thai Government was established the Credit Bureau with the aims of collection data (clearing house of credit information) and protection both credit granters and credit customers from undesirable credits. In 2002, Credit Information Business Act B.E. 2545 was enacted in order to support the functional of Credit Bureau. From this study, the enforcement of Credit Information Business Act B.E. 2545 is found to have problems in many aspects. For example, the defining of the law, the organization management, and the increasing of expend for the financial institutions. Consequently, in this thesis, the author summarizes the problems that are mentioned above, and offers some concluding remarks and recommendation for a further study.